Stereochemistry determination by Powder X-Ray diffraction analysis and NMR spectroscopy residual dipolar couplings - García, Manuela Emila (2009)
For a new steroidal lactol, jaborosalactol 24, isolated from Jaborosa parviflora, NMR spectroscopy residual dipolar couplings and powder X-ray diffraction analysis independently gave the same stereochemistry at C23-C26. Conventional NMR spectroscopic techniques, such as NOE and 3J coupling-constant analysis failed to unambiguously determine this stereochemistry.